Semiotic Analysis of Valak and Lorraine in “The Conjuring 2” Movie - yulia sofiani Zaimar (Scope : Journal of English Language Teaching, 2018)
This paper offers a broad semiotical overview of the horror film, in Conjuring 2. Horror movies aim to bring the audience to deep fear. Therefore, this out of our complacency in the quotidian world, by way of negative emotions such as horror, fear, suspense, terror, and disgust, that is represented in movies. To do so, horror addresses fears that are both universally taboo and that also respond to historically and culturally specific anxieties.Therefore, this journal focuses in to main characters Valak and Loraine, who lead this film to be a horror. This journal is the result of an exploration into the literary reviews of the contemporary horror genre and a semiotic analysis a paranormal, Lorraine. In this journal, the research would discuss a few ethical and semiotic problems related to reality's ability to actually take place within, and break through, fictional representations. This research concerned with the presence of material bodies in the performing sign and code of binnary opposition. This research of signs, codes and conventions in film is called semiotics. Semiotic analysis is a way to explain how an audience makes meaning from codes. This research describes an innovative film studies assignment in which readers can explore still horrorism and Hollywood cinema